Functional recovery of neurological deficit among patients with Orbital Fracture due to Craniofacial Traumas - Khimani, Vashdev; Raja, Riaz Ahmed; Shahzad, Ghazala; Aziz, Peer Asad; Aziz Qureshi, Pir Abdul Ahad; Nasir, Zeeshan (International Journal of Endorsing Health Science Research, 2021)
Background: With recent development in imaging and bone fixation technology, the orbital fracture is now considered an emerging reconstruction technique for the fixation of even the most severe injuries. This study aims to explore the success rate of functional recovery through different orbital approaches in orbital fractures and reconstruction in patients having craniofacial injuries with clinical and neurological deficits. Methodology: This observational study was conducted from 2016 to 2018, at the Department of Neurosurgery, Liaquat University of Medical & Health Sciences (LUMHS). A total number of 30 patients were enrolled through consecutive sampling. The patients with any clinical and neurological deficit were included in this study, while the patients with craniofacial fractures with comorbidities were excluded. The evaluation of clinical and neurological deficits in the admitted patients was noted pre-operatively and re-assessment of the same deficit postoperatively was done during the tenure of 1-6 months. All orbital floor fractures were approached via a sub-ciliary or transconjunctival incision with a supraciliary approach used for all supra orbital injuries. The reconstruction of the fracture was done within 5 to 10 days of admission. Results: A total of 30 patients underwent surgery for the repair of an orbital floor fracture. The mean age observed was 32.09±10.36 years. The patient age range was 20-50 years. Among the patients 22 (73.3.0%) were male and 8(26.7%) patients were female. The improvement of symptoms observed after surgical intervention includes sub-ciliary approach that resides the recovery of diplopia (95%), paraesthesia (75%), enophthalmos (100%) and vertical Dystopia (100%). On the other hand, trans-conjuctival approach resides in the recovery of diplopia (95%), paraesthesia (100%), enophthalmos (100%) and vertical Dystopia (100%). Conclusion: It is concluded that the surgical treatment of orbital fracture shows promising results in the recovery of neurological deficit among patients with crani-o-facial injuries. Moreover, the trans-conjuctival approach holds much promising results in the improvement of infra-orbital para-aesthesia (100%) as compared to the sub-ciliary approach (75%).